2015
DOI: 10.3390/su7067417
|View full text |Cite|
|
Sign up to set email alerts
|

Co-Benefits of Household Waste Recycling for Local Community’s Sustainable Waste Management in Thailand

Abstract: Abstract:The study aimed to evaluate co-benefits in term of GHG reduction, and avoided landfill costs by implementing a community-based management (CBM) program for municipal solid waste (MSW). Two towns of peri-urban settlement in Thailand were investigated in case studies to compare eco-performance between the towns with and without implementation of the CBM program. MSW mass flows together with MSW utilization records were analyzed based on data in year 2013. Climate co-benefits from waste utilization activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 49 publications
0
22
0
1
Order By: Relevance
“…Such an arrangement would involve the active participation of groups with higher abstract knowledge (elderly, women, and the lowest and highest socio-economic categories). Community-based management programs have successfully diverted waste from landfills, as exemplified in Thailand [58]. Replication of such models would go a long way in ensuring the economic, environmental, and social sustainability of waste management in Delhi.…”
Section: Recommendations and Conclusionmentioning
confidence: 99%
“…Such an arrangement would involve the active participation of groups with higher abstract knowledge (elderly, women, and the lowest and highest socio-economic categories). Community-based management programs have successfully diverted waste from landfills, as exemplified in Thailand [58]. Replication of such models would go a long way in ensuring the economic, environmental, and social sustainability of waste management in Delhi.…”
Section: Recommendations and Conclusionmentioning
confidence: 99%
“…It is thus also indicated that RW 4 has a higher level of community participation with regard to the care and maintenance of the environment, and it appears that these RW4 groups have more concern for the environment than those of the other RWs. The community-based waste management is beneficial to reducing the household waste and will improve the local economy through community collaboration [31].…”
Section: % -90%mentioning
confidence: 99%
“…Water resource is the chief causes where it is being hired in most of assessments of management [12,16], followed by forest management [14,15], community services [1,2], e-waste and solid management [16,17,18], etc. For solid waste management, CBM events are hired for both Municipal Solid Waste Management (MSW) or regular governmental services [19,20] with Explicit Waste Management Services (EWMS) [21]. Under MSW gatherers collect electronic and additional garbage from houses, and sort and achieve wastes [10].…”
Section: Reviews Of Literaturementioning
confidence: 99%